Simvastatin Combined with Antioxidant Attenuates the Cerebral Vascular Endothelial Inflammatory Response in a Rat Traumatic Brain Injury. (11th June 2014) - Wang, Kuo-Wei; Wang, Hao-Kuang; Chen, Han-Jung; Liliang, Po-Chou; Liang, Cheng-Loong; Tsai, Yu-Duan; Cho, Chung-Lung; Lu, Kang
Abstract : Traumatic brain injury (TBI) leads to important and deleterious neuroinflammation, as evidenced by indicators such as edema, cytokine production, induction of nitric oxide synthase, and leukocyte infiltration. After TBI, cerebral vascular endothelial cells play a crucial role in the pathogenesis of inflammation. In our previous study, we proved that simvastatin could attenuate cerebral vascular endothelial inflammatory response in a rat traumatic brain injury. This purpose of this study was to determine whether simvastatin combined with an antioxidant could produce the same effect or greater and to examine affected surrogate biomarkers for the neuroinflammation after traumatic brain injury in rat. In our study, cortical contusions were induced, and the effect of acute and continuous treatment of simvastatin and vitamin C on behavior and inflammation in adult rats following experimental TBI was evaluated. The results demonstrated that simvastatin combined with an antioxidant could provide neuroprotection and it may be attributed to a dampening of cerebral vascular endothelial inflammatory response.